Beliefs about Legality and Benefits for Mental Health. (June 2022) - Upenieks, Laura; Sendroiu, Ioana; Levi, Ron; Hagan, John
Research on mental health pays increasing attention to the influence of social institutions on subjective well-being over the life course. Yet little research has considered how belief in the promise of legal institutions may have beneficial effects for well-being. Through structural equation models of longitudinal data, our findings suggest that belief in the neutrality and fairness of legal institutions has salutary effects for mental health net of social and economic status and across individuals from a wide range of ethnic groups. By combining research in the sociology of mental health, cultural sociology, social psychology, and the sociology of law, we extend the emerging literature on the institutional determinants of mental health by including attention to law as one of the central organizing institutions of social life.